الخصائص السيكومترية لمقياس الذكاء الوجداني لدى المشرفين التربويين في سلطنة عمان : Psychometric Properties of the Emotional Intelligence Scale for Educationl Supervisors in the Sultanate of Oman - Al Hosni, Salim Khalfan Ali; Mohamed Adnan, Mohamad Azrien (Al-Basirah Journal, 2025)
Accordingly, the study aimed to identify the validity indicators of the Emotional Intelligence Scale among educational supervisors in the Sultanate of Oman. In addition, the study aimed to identify the reliability indicators of the Emotional Intelligence Scale among educational supervisors in the Sultanate of Oman. The Emotional Intelligence Scale was employed on a sample of (173) male and female supervisors distributed over all educational governorates. The results showed that the validity indicators of the Emotional Intelligence Scale of educational supervisors in the Sultanate of Oman had achieved significant correlations at the level of 0.01 with the degrees of the dimension to which they belong. In addition, the dimensions achieved significant correlations at the level of 0.01 with the total score of the scale. This confirms the internal consistency and construct validity of the scale. The results also showed that the reliability indicators of the emotional intelligence scale of the educational supervisors in the Sultanate of Oman were generally characterized by a good degree of stability. This confirms the alpha’s Cronbach stability and the split-half stability. Thus, the scale can be relied upon in application to other samples. The study recommended the need to develop measures of emotional intelligence for administrators, educational supervisors, and teachers. In addition, there is a need to develop training packages aimed at imparting emotional intelligence skills to various educational groups and striving to include emotional intelligence in teacher and leader preparation programs.